Long‐term clinical impact of PSA surge in castration‐resistant prostate cancer patients treated with abiraterone. Issue 9 (20th April 2017) - Conteduca, Vincenza; Caffo, Orazio; Lolli, Cristian; Aieta, Michele; Scarpi, Emanuela; Bianchi, Emanuela; Maines, Francesca; Schepisi, Giuseppe; Salvi, Samanta; Massari, Francesco; Carrozza, Francesco; Veccia, Antonello; et al.
Abstract : Background: Early changes in PSA have been evaluated in association to treatment outcome. The aim of this study was to assess PSA surge phenomenon in castration‐resistant prostate cancer (CRPC) patients treated with abiraterone and to correlate those variations with long‐term treatment outcome. Patients and Methods: We retrospectively evaluated 330 CRPC patients in 11 Italian hospitals, monitoring PSA levels at baseline and every 4 weeks. Other clinical, biochemical and molecular parameters were determined at baseline. We considered PSA surge as PSA increase within the first 8 weeks from starting abiraterone more than 1% from baseline followed by a PSA decline. The log‐rank test was applied to compare survival between groups of patients according to PSA surge. The impact of PSA surge on survival was evaluated by Cox regression analyses. Results: A total of 330 patients with CRPC, median age 74 years (range, 45–90), received abiraterone (281 chemotherapy‐treated and 49 chemotherapy‐naïve). PSA surge was observed in 20 (7%) post‐chemotherapy and 2 (4%) chemotherapy‐naïve patients. For overall patients presenting PSA surge, timing of PSA peak from baseline was 5 ± 1.8 weeks and PSA rise from baseline was 21 ± 18.4%. The overall median follow‐up was 23 months (range 1–62). No significant differences in progression‐free survival and overall survival were observed between patients with and without PSA surge ( P = 0.16 and =0.86, respectively). In addition, uni‐ and multivariate analyses showed no baseline factors related to PSA surge. Conclusion: PSA surge occurs in both chemotherapy‐treated and chemotherapy‐naïve patients treated with abiraterone resulting, however, in no long‐term impact on outcome. Physicians and patients should be aware of PSA surge challenge to prevent a premature discontinuation of potentially effective therapy with abiraterone. Further larger and prospective studies are warranted to investigate this not infrequent phenomenon.